PERSPEKTIF DRAMATURGI DALAM KASUS MUCIKARI DI KALANGAN MAHASISWA KAWASAN KAMPUS PANAM KOTA PEKANBARU - Sandi, Perestian Aris; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research was conducted in the District Charming Pekanbaru City. This study, entitledPerspectives Dramaturgy in Case Pimps Among College Students Panam Pekanbaru Cityarea. The purpose of this study was to determine the background of the social life of a studentwho works as a pimp for chickens campus in the District Handsome. Topics focus of thisresearch is the process of pimping for chickens student campus in dramaturgical perspectivein District Charming. The research subjects studied were pimps students in the district asmany as three people Handsome research subjects. The author uses descriptive qualitativemethod and the data were analyzed qualitatively using Snowball Sampling taking technique.Data instrument is observation, interview, and documentation. Research conducted onstudents who work as a pimp for chickens campus in the District Handsome get finding thebackground of the social life of students is coming from families who have economicproblems is low, every pimp backgrounds unstable economic before becoming pimps, andevery pimp has been used to living with promiscuity that do not have restrictions norm.Pimps working interaction process includes the characteristics and performance of everydaypimping on campus and the neighborhood.In both these environments are very smart pimpsadapt without arousing suspicion by those around him. Pimps working process including howto serve consumers and the system works. In serving consumers pimping is not arbitraryreceiving customers, pimps will seek approval from his campus chicken first, then approvedchicken campus then the consumer will be presented regarding the payment and prostitutionservices provided.Keywords: Perspectives Dramaturgy, Pimps Students